Pelatihan Pembuatan Video Ajar Dengan Open Broadcaster Software Bagi Guru Di SMP Negeri 1 Karang Bahagia Kabupaten Bekasi - Ali Idrus; Lipur Sugiyanta (LPPM STIKOM Tunas Bangsa, 2021)
Karang Bahagia Subdistrict, Bekasi Regency, West Java Province which enforces PSBB. Based on Bekasi Regent Regulation No. 37 of 2020 concerning the implementation of Large-Scale Social Restrictions (PSBB) in handling the corona virus disease in Bekasi Regency, applies to all elements of activity. In Article 6 Bekasi Regent Regulation No. 37 of 2020, it is also explained that the process of implementing learning in schools is carried out at home or where students live through distance learning. Many teachers at SMP Negeri 1 Karang Bahagia, Bekasi Regency, do not understand how to make learning media that can be used for distance learning. The face-to-face learning method that has been done so far must be changed into a digital format that displays text, audio and visual so that the subject matter can be delivered optimally. Therefore, assistance and training are needed for teachers in making teaching videos with software commonly used in presenting online video broadcasts, namely Open Broadcaster Software (OBS). based on the results of the pre-test and post-test given to 144 training participants, 59 % of participants' knowledge increased related to video-making techniques. participants' knowledge increases regarding video-making techniques.